"Giving back is typical African culture": Narratives of give-back from young African graduates (Journal of Student Affairs in Africa, 2023)
This article presents a collection of narrative examples on how a cohort of African graduates, who are beneficiaries of a scholarship from a global foundation, understand and practice giving back. The scholarship programme aims to cultivate and support a network of like-minded young leaders who are committed to giving back by providing training and mentorship that reinforces the core values of transformative leadership and a commitment to improving the lives of others. To investigate these ideas, the Human Sciences Research Council is tracking recent graduates of the scholarship programme using a longitudinal cohort study design consisting of a tracer study, annual qualitative interviews with scholarship alumni, and smaller collaborative enquiries. Beginning in 2019 and tracking alumni for a five-year period, the study involves alumni from seven study sites. Findings from the study show that alumni exhibit a strong sense of social consciousness including an alignment of their understanding and practices of give-back with deeply embedded African notions of give-back as a ‘ripple effect’, reciprocity and ubuntu. Alumni acknowledged that there was not only one way to give, indicating that they participated in give-back in relation to their capacity, usually beginning with contributions to the family. As they became more established in their careers, their sphere of give-back increased with their reach expanding to the broader community. A low proportion of alumni felt that they were making an impact on an institutional or systemic level. Findings also show the impactful position that university partners hold in fostering give-back engagement among students and their potential role in supporting alumni after graduation. The article argues that nurturing social consciousness in young people and an understanding of give-back as collective movement building can contribute to solving development and social justice problems in Africa.